Examination the Interaction between the Composition of a Theoretical Ecosystem and the Increase in the Atmospherical CO2 Level (Hungarian Journal of Industry and Chemistry, 2010)
The development of automotive industries and energetics has a large impact on the carbon-dioxide level in the atmosphere and therefore on the climate change process. There is a continuous cycle and flow of inorganic compounds between the atmosphere and the ecosystems, therefore the anthropogenic affects (such as CO2 emission) strongly modify the activities of ecosystems. The modified activities are as follows: fluxes of the photosynthesis, CO2 emission of the soil or the quantity of dissolved organic compounds in the ocean. These activities could have a feedback on the climate controlling the compounds of the atmosphere and therefore on the temperature of the Earth. The most important anthropogenic green-house gas (GHG) is the carbon-dioxide. The global CO2-level has an increase from 280 ppm (before industrial era) to 380 ppm (by 2008). The annual fossil CO2-emission was 6.0–6.8 Pg C in the 1990s, and 6.9–7.5 Pg C in 2000–2005. There is positive correlation between the amount of green house gases in the atmosphere and the temperature, so the larger the increase in the GHG-level the higher the global temperature in the Earth. The ecosystems could control the climate (precipitation, temperature) in a way that an increase in the atmosphere component (e.g. CO2 concentration) induces the processes in biosphere to decrease the amount of that component through biogeochemical cycles. These feedbacks could affect the climate either on positive or negative ways. In our research the answers of a theoretical freshwater ecosystem are examined on the change in the value and the fluctuation of the temperature. Our aim is to show a simple ecological model related to this feedback mechanism, and to examine the feedback ability of the theoretical ecosystem to the temperature of the atmosphere.
Keywords: theoretical ecosystem; feedback; climate modelling; climate change; control